The effect of age on the blood proteinogram of Chinese goose (Anser cygnoides) - Schmidt, Elizabeth Moreira Dos Santos [UNESP]; Campioni, Josie Maria [UNESP]; Paulillo, Antonio Carlos [UNESP]; Denadai, Janine [UNESP]; Santana, André Marcos [UNESP]; Testi, Alan Jonathan Pereira [UNESP] (My University, 2008)
The influences of age on serum protein values were investigated in juvenile Chinese goose. Statistical comparisons were made for differences in values among different ages. These samples were used to determine baseline data on serum total protein, albumin, globulins and albumin/globulin ratio. Significant variations were not observed in the analyses in relation to the age of birds for serum total protein, albumin and globulins. The albumin/globulin ratio showed significant difference among 21 and 49 day-old Chinese geese. © Asian Network for Scientific Information, 2008.
Keywords: Albumin; Anser cygnoides; Blood proteinogram; Total serum protein; Anser; Aves